2019
DOI: 10.7163/gpol.0155
|View full text |Cite
|
Sign up to set email alerts
|

Intensive tourist-related urbanisation impacts on a mountain village: The case study of Veľká Lomnica in Slovakia

Abstract: Abstrakt: A key feature of contemporary tourism is massive investment on the part of developers in tourism-related urbanisation, with this made most manifest in the construction of recreational apartment houses, and the expansion of ski slopes and golf courses. For obvious reasons, such activities are directed at traditional centres of tourism, which respond to the current trend towards hedonism present in society. However, major development activity has also taken place in municipalities in which tourism onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There, it can represent not only housing as such but also recreational housing (e.g. second homes) which has been lately experiencing substantial growth in ECE (Petrikovicova et al, 2019), even though its impact in the locality was previously found to be negative (Hajimirrahimi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There, it can represent not only housing as such but also recreational housing (e.g. second homes) which has been lately experiencing substantial growth in ECE (Petrikovicova et al, 2019), even though its impact in the locality was previously found to be negative (Hajimirrahimi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Streifeneder & Omizzolo, 2017;Vidović & Dželetović, 2019;Abellán & Martinez, 2021). One thing is for sure, over the years, the mountain areas have suffered intense metamorphosis to satisfy the ever-changing requirements (Bonadonna et al, 2017;Petrikovičová et al, 2019); thus, they have transformed from important areas of exploitation of natural resources into areas where tourism plays a key role (Ritchins et al, 2016). Due to their aesthetic beauty, natural and cultural landscapes that harmoniously intertwine (Więckowski, 2020), various possibilities to spend leisure time and the aura of mystery (Hull, 2016), the moutains attract millions of tourists each year.…”
Section: Introductionmentioning
confidence: 99%
“…We perceive a tourist landscape according to Gunn [4] as the total physical and visual environment utilized by all tourism activities, including the whole context and infrastructure of tourism development, such as transportation, services, information, direction and, generally speaking, all such developments that attract people to a destination. Increasingly, the use of the tourist type of landscape is characterized as insensitive in terms of natural components [5][6][7], as well as the local population [8][9][10].…”
Section: Introductionmentioning
confidence: 99%